2015
DOI: 10.1155/2015/807876
|View full text |Cite
|
Sign up to set email alerts
|

Tree Diversity and Community Composition of the Tutong White Sands, Brunei Darussalam: A Rare Tropical Heath Forest Ecosystem

Abstract: Bornean heath (Kerangas) forests are a unique and increasingly rare tropical forest ecosystem that remains little studied. We quantified tree floristic diversity in Kerangas forests in the Tutong White Sands, Brunei Darussalam, and investigated the influence of soil and environmental variables on community composition. Six 20 m × 20 m plots were established, where all trees of ≥5 cm diameter at breast height (DBH) were identified and measured to determine stem diameter and basal area. We determined pH, gravime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…At Gunung Mulu (Sarawak, Malaysia), Newbery & Proctor (1984) focussed on differences in soil chemistry and found species distribution to be associated with differences in soil organic C and CEC, whilst Miyamoto et al (2003) found the most abundant tree species to be weakly associated with humus depth in a Central Kalimantan (Indonesia) heath forest. Din et al (2015), instead, ascribed variation in a Bruneian heath forest community to soil N concentration but highlighted that other topographic and edaphic variables, not considered in their study, might also have an effect on species distributions.…”
Section: Introductionmentioning
confidence: 92%
“…At Gunung Mulu (Sarawak, Malaysia), Newbery & Proctor (1984) focussed on differences in soil chemistry and found species distribution to be associated with differences in soil organic C and CEC, whilst Miyamoto et al (2003) found the most abundant tree species to be weakly associated with humus depth in a Central Kalimantan (Indonesia) heath forest. Din et al (2015), instead, ascribed variation in a Bruneian heath forest community to soil N concentration but highlighted that other topographic and edaphic variables, not considered in their study, might also have an effect on species distributions.…”
Section: Introductionmentioning
confidence: 92%
“…Understanding this would give an added perspective on how specialized archaea are with respect to habitat in the tropics. Given that the ecosystem of white sand forests is widely considered to be strongly limited by nitrogen supply (in addition to other nutrients) [19,21] and that soil archaea play an important part in ammonia oxidation [22][23][24][25][26], understanding the archaeal ecology of white sand forests and how it differs may ultimately have a role in understanding this peculiar ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The term 'heath forest' is used to describe a tropical rainforest comprising less tall trees with smaller leaves in comparison with those of the more widespread Tropical Lowland Evergreen Rain Forest (Whitmore 1984). The study at heath forest has been focused on environmental condition (before and after mined land), diversity of vegetation, and its correlation with soil properties (Din et al 2015;Oktavia et al 2015). However, there has been less study on the exploration of the potential microbial component at heath forest, including white rot fungi laccase-producer.…”
Section: Discussionmentioning
confidence: 99%
“…The heath or kerangas forest has been long known to exist in Kalimantan and Sumatra Islands. Heath forests are a type of seasonal lowland tropical rainforest that develop in dryland sites with predominantly podzolized, highly acidic, and sandy soils (Din et al 2015). This study aimed to investigate a potential local isolate of white rot fungi, Leiotrametes flavida strain ZUL62, from Bangka heath forest in term of its capability to decolorize RBBR anthraquinone dye which is used in the textile industry and represents an important class of toxic and recalcitrant organopollutants.…”
Section: Introductionmentioning
confidence: 99%